Electrochemical functionalization strategy for chemical vapor deposited graphene on silicon substrates: grafting, electronic properties and biosensing. (5th September 2019) - Sarmiento, Viviana; Oropeza-Guzmán, Mercedes Teresita; Lockett, Malcolm; Chen, Wenjun; Ahn, Seungbae; Wang, Jiaying; Vazquez-Mena, Oscar
Abstract: Herein, we present an electrochemical functionalization strategy for high quality single-layer and multilayer chemical vapor deposited (CVD) graphene directly on a Si/SiO2 chip facilitating electronic interfacing. This method avoids oxidation and tearing of graphene basal planes. We demonstrate effective functionalization by D-(+)-biotin (Bio), 4-(phenyldiazenyl)-aniline (Dz), and gallic acid (Gall) using cyclic voltammetry. Raman spectroscopy and XPS are used to demonstrate effective functionalization. In order to evaluate the effect of the electrochemical functionalization on graphene properties, DC electrical conductivity, XPS, mobility, and carrier density analysis are presented. We show that this functionalization strategy does not degrade graphene mobility (10 3 cm 2 V −1 s −1 ). After functionalization we observe a rise in Fermi level of ∼0.06 eV. In addition, we prove sensing capabilities with a CVD graphene monolayer on the biotin/avidin system by electrical resistance measurements and electrochemical impedance spectroscopy reaching a detection of 2.5 ng ml −1 . This paper demonstrates an effective strategy to functionalize high quality CVD graphene on a chip compatible with an electronic interface readout.